The Effect of the Ideal Food Pyramid on Gut Microbiota in Rheumatoid Arthritis Patients - Ülger Kaçar Mutlutürk; Betül Çiçek; Gizem Cengiz (Life)
Background: The gut microbiota composition of rheumatoid arthritis (RA) patients differs from healthy people, and diet is among the powerful environmental determinants that can alter the microbiota. The purpose of this clinical research was to identify the effect of the Ideal Food Pyramid on gut microbiota in RA, as well as its impact on disease activity, biochemical findings and anthropometric measurements. Methods: Thirty patients diagnosed with RA that met the inclusion criteria were randomized into diet and control groups and followed for 12 weeks. The gut microbiota composition was indicated by 16SrRNA gene sequencing. Results: At the end of this study, Simpson, Shannon and Chao-1 indices were higher in the diet group (16) than in the control group (14), although not significantly (p > 0.05). In the diet group, at phylum levels, the abundance of Bacteroides decreased while the abundance of Firmicutes increased. At species level, Prevotella copri, Bacteroides fragilis, Prevotella stercorea, Bacteroides uniformis decreased, while Faecalibacterium prausnitzii, Roseburia faecis, Bacteroides ovatus, Akkermansia muciniphila, Coprococcus eutactus, Gemmiger formicilis, Ruminococcus bromii, and Bifidobacterium longum species increased in the diet group. Conclusions: The Ideal Food Pyramid has been determined to have many clinical benefits for RA patients, especially for the gut microbiota.